Cloning and heterologous expression of Dalpha4, a Drosophila neuronal nicotinic acetylcholine receptor subunit: identification of an alternative exon influencing the efficiency of subunit assembly. - Lansdell, S.J.; Millar, N.S. (Neuropharmacology, 2000)
A neuronal nicotinic acetylcholine receptor (nAChR) subunit, Dalpha4, has been identified and cloned from the fruit fly Drosophila melanogaster, together with several alternatively spliced transcripts. Intron-exon boundaries within the gene encoding Dalpha4 (nAcRalpha-80B) have been identified by comparison of cDNA and genomic sequence data. The influence of amino acids encoded by alternatively spliced exons upon nicotinic radioligand binding and subunit-subunit co-assembly has been examined by heterologous expression in Drosophila S2 cells. The efficiency of subunit assembly has been shown to be influenced by amino acids surrounding the highly conserved 15 amino acid cysteine-loop motif within the N-terminal extracellular domain of the nAChR Dalpha4 subunit. Extensive use has been made of publicly available data determined by the Berkeley Drosophila Genome Project (BDGP). This includes expressed sequence tag (EST) data as well as whole-embryo in situ hybridisation and polytene chromosome in situ hybridisation data. BDGP in situ hybridisation data suggests that the Dalpha4 mRNA is expressed within Drosophila brain and ventral nerve cord and demonstrates that the gene encoding this nAChR subunit is located at position 80B on chromosome 3. The relationship between Dalpha4 and other previously cloned nAChR subunits has been examined and the implications for the nomenclature of insect nAChRs is discussed.